NAVIGATING THE DIGITAL DILEMMA: PROTECTING INDONESIAN CHILDREN FROM CYBERCRIME - Yusrizal, Yusrizal; Saputra, Ferdy; Iskandar, Hadi; Asmara, Romi; Muhammad Rasyid, Laila (Universitas Syiah Kuala, 2025)
Children has been increasingly vulnerable to a multitude of cybercrimes in Indonesia. These include alarming issues such as online grooming, sexual exploitation, cyberbullying, and identity theft. This situation not only presents significant legal challenges but also represents a profound ethical crisis within Indonesias evolving digital landscape. This article utilizes a normative juridical approach alongside a conceptual framework to articulate legal arguments surrounding these pressing concerns. While regulatory measures exist, such as the Electronic Information and Transactions (ITE) Law and the Child Protection Law, their enforcement remains fragmented and often inadequate to tackle the constantly changing nature of digital threats. The ethical dimensions of this crisis cannot be overlooked, as they intertwine with corporate responsibility, parental awareness, and systemic inaction. Such issues amplify the risks that children face online. This study asserts that the combination of legal deficiencies and ethical oversight creates a substantial protection gap that demands a coherent and interdisciplinary response. To effectively safeguard children in the digital age, it is crucial to strengthen institutional capacities, integrate digital literacy within educational curricula, and adopt child-centered approaches to digital governance. By doing so, we can work towards ensuring that the rights, dignity, and safety of children are prioritized and protected in Indonesia.